Modeling the Social and Spatial Proximity of Crime: Domestic and Sexual Violence Across Neighborhoods - Kelling, Claire (Journal of quantitative criminology, 2021)
Our goal is to understand the social dynamics affecting domestic and sexual violence in urban areas by investigating the role of connections between area nodes, or communities. We use innovative methods adapted from spatial statistics to investigate the importance of social proximity measured based on connectedness pathways between area nodes. In doing so, we seek to extend the standard treatment in the neighborhoods and crime literature of areas like census blocks as independent analytical units or as interdependent primarily due to geographic proximity.